2021
DOI: 10.3390/ani11113165
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lycopene Supplementation Could Alleviate Aflatoxin B1 Induced Intestinal Damage through Improving Immune Function and Anti-Oxidant Capacity in Broilers

Abstract: The present study aims to evaluate the effects of lycopene (LYC) supplementation on the intestinal immune function, barrier function, and antioxidant capacity of broilers fed with aflatoxinB1 (AFB1) contaminated diet. A total of 144 one-day-old male Arbor Acres broilers were randomly divided into three dietary treatment groups; each group consisted of six replicates (eight birds in each cage). Treatments were: (1) a basal diet containing neither AFB1 nor LYC (Control), (2) basal diet containing 100 µg/kg AFB1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 64 publications
4
23
0
Order By: Relevance
“…In the present study, AFB 1 significantly increased the concentrations of MDA and decreased the antioxidant enzyme activities of T-SOD, GSH-Px, GST, and CAT in the liver, jejunum, and the plasma of broilers when compared with the CON. These results are in consistent with previous studies, which demonstrated that different dosage of AFB 1 decreased the activity of antioxidant enzymes, increased the lipid peroxidation, and inhibited the antioxidant capacity of broilers (14,15,54,55). Recently, researchers have been interested in the usage of antioxidants to counter the toxic effects of aflatoxins (56).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, AFB 1 significantly increased the concentrations of MDA and decreased the antioxidant enzyme activities of T-SOD, GSH-Px, GST, and CAT in the liver, jejunum, and the plasma of broilers when compared with the CON. These results are in consistent with previous studies, which demonstrated that different dosage of AFB 1 decreased the activity of antioxidant enzymes, increased the lipid peroxidation, and inhibited the antioxidant capacity of broilers (14,15,54,55). Recently, researchers have been interested in the usage of antioxidants to counter the toxic effects of aflatoxins (56).…”
Section: Discussionsupporting
confidence: 92%
“…The recommended Mn content for broilers is 120 mg/kg during 1–3 weeks and 100 mg/kg during 4–6 weeks by the Feeding Standard of Chicken in China. Additionally, we searched recent related articles on broiler experiments in Animals and also found that the amount of added Mn in the diet was around 100 mg/kg [ 18 , 19 , 20 , 21 , 22 ]. So we added 100 mg/kg Mn in the form of MnSO 4 as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Corn treated with lycopene increased the level of immunoglobulin G in sheep's blood, which facilitated passive immunity transfer to newborn lambs (Fallah et al 2021). Dietary lycopene supplementation may increase antioxidant activity and ameliorate AFB1-induced intestinal immune function and barrier function impairment in the intestinal mucosa (Sarker et al 2021). In diabetic rats, lycopene has anti-anemic properties and improves immunity.…”
Section: A Dysfunctional Immune Response To Covid-19 Could Be Enhance...mentioning
confidence: 99%